Knowledge of puerperas about analgesia of normal delivery in public maternity in the interior of Rio Grande do Norte, Brazil (Research, Society and Development, 2021)
Objective: To assess the knowledge of postpartum women about analgesia in vaginal labor, as well as the association between the existence of this information and the decision and outcome regarding the type of delivery in Ana Bezerra University Hospital (HUAB), in Santa Cruz, Rio Grande do Norte, Brazil. Methodology: The model of this study was descriptive and cross-sectional, with a quantitative approach. The sample consisted of puerperal women attended at the HUAB maternity hospital. Data were collected through direct interviews, with the completion of a structured questionnaire, as well as a review of medical records. Results: 99 puerperal women were interviewed. It was observed that 78.8% had vaginal delivery and there was a statistically significant relationship between this type of vaginal delivery and higher education level, income higher than the minimum wage and paid work. It was found that only 22.2% knew about the availability of analgesia for vaginal delivery. The pregnant woman's decision about the type of delivery was also associated with the occurrence of vaginal delivery, but there was no association between knowledge of the existence of analgesia during labor in the maternity ward with the mother's decision or with the performance of vaginal delivery. Conclusion: The rate of knowledge about the availability of analgesia for childbirth was low, consistent with results from other developing countries. Maternal knowledge about the availability of pain relief during labor was related to education level, income, and paid work, but was not associated with the maternal decision for vaginal delivery or with this type of parturition.